Homeownership, Political Participation, and Social Capital in Post‐Communist Countries and Western Europe. (5th January 2020) - Huber, Peter; Montag, Josef
SUMMARY: We study whether the positive effects of homeownership on political participation and social capital, found in developed market economies, extend to post‐communist countries. We use the privatization of publicly‐owned housing in post‐communist countries as an exogenous source of variation of homeownership status to identify its impact on political participation and social capital formation. We find that homeownership is strongly related to higher participation in local‐level and national elections. In post‐communist countries, homeownership is also related to higher social trust. However, the positive association between homeownership and volunteering found in developed market economies does not extend to post‐communist countries. Together, our results corroborate that homeownership is associated with positive social benefits. However, these effects are highly heterogeneous and context‐dependent.